COVID-19 Pandemic: What else can I do? - Flórez G., Lujhon G. (2020)
In these last weeks about by the COVID-19 pandemic, a phrase has become popular in Europe that, translated from its Italian antive says: “Remember that our grandparents were ordered to go to war; ¡all that is asked of us, is just to stay on the couch!”.Although scientists from different countries and organizations are working rapidly to develop an effective vaccine and to have drugs that help treat this disease, until now the best thing to do to prevent the rapid spread of the virus is through measures hygienic and preventive distancing. However, many of us wonder what else we can do besides avoiding or delaying infection? Is it possible to improve our chances of successfully dealing with this disease?